2022
DOI: 10.1021/acs.jpclett.1c03907
|View full text |Cite
|
Sign up to set email alerts
|

Water-Induced Restructuring of the Surface of a Deep Eutectic Solvent

Abstract: We study the molecular-scale structure of the surface of Reline, a DES made from urea and choline chloride, using heterodyne-detected vibrational sum frequency generation (HD-VSFG). Reline absorbs water when exposed to the ambient atmosphere, and following structure-specific changes at the Reline/air interface is crucial and difficult. For Reline (dry, 0 wt %, w/w, water) we observe vibrational signatures of both urea and choline ions at the surface. Upon increase of the water content, there is a gradual deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…The decrease in the eutectic point of the BTEAB/urea DES to around À15 1C may hinder the use of DES-H 2 O/DMSO as a solvent in organic, electrochemical, and other applications. [140][141][142][143][144]…”
Section: C:imentioning
confidence: 99%
“…The decrease in the eutectic point of the BTEAB/urea DES to around À15 1C may hinder the use of DES-H 2 O/DMSO as a solvent in organic, electrochemical, and other applications. [140][141][142][143][144]…”
Section: C:imentioning
confidence: 99%
“…Many DESs contain water, and even when dried to remove water, a trace amount of water is an unavoidable impurity . There are a few reports of bulk DES structure as a function of water content and fewer reports of interfacial structure. ,,,, …”
Section: Effect Of Water Content On Interfacial and Bulk Structure In...mentioning
confidence: 99%
“…Experimental data show that interfacial structure, similar to bulk structure, is retained at high water contents. 62,66 At the gas/DES interface, Bakker et al observed a gradual depletion of urea as well as enrichment and alignment of choline cations at the surface with increasing water contents of up to 40 wt %. 66 At 60 wt % water, the interfacial structure of the DES is indistinguishable from that of pure water.…”
Section: ■ Effect Of Water Content On Interfacial and Bulk Structure ...mentioning
confidence: 99%
See 1 more Smart Citation
“…53 Their results from vibrational SFG spectroscopy have indicated the surface of the mixture above 60 wt % H 2 O resembles the spectrum of pure water. 53 This observation agrees with our result from aerosol XPS spectra (Figure 4b). The XPS spectrum of 80 wt % H 2 O mixture (Figure 4a) is almost indistinguishable from the spectrum of pure glycerol (Figure S1) or glycerol−water mixtures, indicating minor surface presence of Ch + at higher water content.…”
mentioning
confidence: 99%